Data logger device applicability for wheelchair tennis court movement - Sindall, P.; Lenton, J.; Cooper, R.; Tolfrey, K.; Goosey-Tolfrey, V. L. (Journal of Sports Sciences, 2015)
Assessment of movement logging devices is required to ensure suitability for the determination of court-movement variables during competitive sports performance and allow for practical recommendations to be made. Hence, the purpose was to examine wheelchair tennis speed profiles to assess data logger device applicability for court-movement quantification, with match play stratified by rank (HIGH, LOW), sex (male, female) and format (singles, doubles). Thirty-one wheelchair tennis players were monitored during competitive match play. Mixed sampling was employed (male = 23, female = 8). Friedman`s test with Wilcoxon signed-rank post hoc testing revealed a higher percentage of time below 2.5 m/s [<2.5 vs. =2.5 m · s-1: 89.4 (5.0) vs. 1.2 (3.5)%, Z = -4.860, P < 0.0005, r = 0.87] with the remaining time [9.0 (4.9%)] spent stationary. LOW-ranked players were stationary for longer than HIGH-ranked counterparts [12.6 (8.7) vs. 8.2 (5.1)%, U = 30.000, P = 0.011, r = 0.46] with more time at low propulsion speeds (<1.0 m · s-1). HIGH-ranked and doubles players spent more time in higher speed zones than respective counterparts. Females spent more time in the 1.0-1.49 m/s zone (U = 48.000, P = 0.047, r = 0.36). Regardless of rank, sex or format, propulsion speeds during wheelchair tennis match play are consistent with data logger accuracy. Hence, data logging is appropriate for court-movement quantification.